International student transitioning experiences: Student voice - Wignell, Peter; Ashton-Hay, S.; Evans, K. (Association for Academic Language and Learning, 2016)
As Australian higher education institutions seek to internationalise and in-crease enrolments of international students, the student experience is crucial for ensuring a sustainable future via delivery of quality learning, develop-ment of English language standards and retention of enrolments. This project aimed to capture student voice in order to better understand the early chal-lenges students face, the support they value and the adequacy of current ser-vices benchmarked against the Good Practice Principles (GPP) (DEEWR, 2009). With a focus on English language proficiency, a mixed method ap-proach surveyed 140 students across three campuses, followed by focus groups to capture student voice and provide a current snapshot of interna-tional student experiences and perceptions. The key findings confirm that in-ternational students are challenged with writing, speaking and listening and also that they believed more opportunities to interact using English would benefit them. Another finding indicated the incongruity between prior learn-ing experiences and basic academic literacy skills as well as technology for learning skills. The project found that although the university has taken steps towards meeting the GPP, a broader university-wide approach is needed. Recommendations include providing technology-essentials seminars; em-bedding opportunities in the curriculum for students to develop communica-tion skills, cultural competence and academic literacy; and increasing col-laboration between content staff and academic language and learning spe-cialists. Academic Skills support was one of the university services most valued by international students, and they particularly appreciated team teaching by Academic Skills staff and content lecturers together.